Apakah Ketahanan Pangan dapat Menurunkan Pekerja Anak di Indonesia? - Putri, Nabila Aurelliza Candrika; Rahmat, Ervan Nur; Primasrani, Byun Jiye; Safitri, Junita Sholekhatun; Akbar, Fadly Muhamad; Budiasih, Budiasih (Seminar Nasional Official Statistics, 2023)
Child labor is a global issue and one of the national problems that requires immediate and continuous action. According to FAO, there is a link between poverty and food security for child labour. Therefore, this research was conducted with the aim of seeing whether food security, which is approached by the variables of poverty, food expenditure, length of education, and income, has an effect on child labour. The method used is panel data regression which in the end the FEM model was chosen as the best model in achieving the research objectives. In this study, the results showed that empirically the poor had a positive effect, spending on food had a negative effect, length of education had a positive effect, and income per capita had a negative effect. So it can be said that food security has an influence on child labour.